2012
DOI: 10.1136/bmjopen-2012-001637
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of cocaine consumption in the community: a critical comparison of the results from three complimentary techniques

Abstract: ObjectivesA range of approaches are now available to estimate the level of drug use in the community so it is desirable to critically compare results from the differing techniques. This paper presents a comparison of the results from three methods for estimating the level of cocaine use in the general population.DesignThe comparison applies to; a set of regional-scale sample survey questionnaires, a representative sample survey on drug use among drivers and an analysis of the quantity of cocaine-related metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…The last decade has seen the emergence and refinement of wastewater-based epidemiology (WBE), which relies on quantitative measurement of specific biomarkers of illicit drug use in wastewater. Presented as a complementary approach to current surveillance methods (Amundsen and Reid, 2014;Been et al, 2015;Bramness et al, 2014;Reid et al, 2012Reid et al, , 2011, WBE has received much attention. Although further developments will most probably refine it in the near future, WBE already enables the gathering of unique spatio-temporal information about consumption (Ort et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The last decade has seen the emergence and refinement of wastewater-based epidemiology (WBE), which relies on quantitative measurement of specific biomarkers of illicit drug use in wastewater. Presented as a complementary approach to current surveillance methods (Amundsen and Reid, 2014;Been et al, 2015;Bramness et al, 2014;Reid et al, 2012Reid et al, , 2011, WBE has received much attention. Although further developments will most probably refine it in the near future, WBE already enables the gathering of unique spatio-temporal information about consumption (Ort et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the estimation of the number of doses or even of individual users based on sewage samples requires a series of assumptions and remains specula tive. Nev er theless, some studies have shown good qualitative agreement between sewage-based estimates and other data (Reid et al 2012). …”
Section: Figurementioning
confidence: 99%
“…This method can detect both traditional drugs and new psychoactive substances, including previously undetected drugs, even at low concentrations [122][123][124][125].…”
Section: Illicit Drugsmentioning
confidence: 99%